The dissection of vertebrates - De Iuliis, Gerardo, 1959-; Pulera, Dino (Academic Press, an imprint of Elsevier, 2019)
This newly revised edition of the most comprehensive manual available continues to offer today's more visually oriented student with a manual combining pedagogically effective text with high-quality, accurate and attractive visual references. This new edition features updated and expanded phylogenetic coverage, revisions to the illustrations and text of the lamprey, shark, perch, mudpuppy, frog, cat, pigeon, and reptile skull chapters, and new sections on amphioxus or lancelet (Branchiostoma, Cephalochodata), a sea squirt (Ciona, Urochordata), shark musculature, a gravid shark, shark embryo, cat musculature, and the sheep heart. Using the same systematic approach within a systemic framework as the first two editions, The Dissection of Vertebrates, 3rd Edition covers several animals commonly used in providing an anatomical transition sequence. Nine animals are covered: amphioxus, sea squirt, lamprey, shark, perch, mudpuppy, frog, cat, and pigeon, plus five reptile skulls, two mammal skulls, and the sheep heart.